Altered temporal expression of DNA repair in hypermutable Bloom's syndrome cells. - Gupta, P K (1984)
The temporal regulation of DNA repair during synchronous cell proliferation was examined in normal human skin fibroblasts and in Bloom's syndrome skin fibroblasts. Normal human cells regulated DNA repair in a defined temporal sequence prior to the induction of DNA replication. Nucleotide-excision repair was stimulated prior to the induction of base-excision repair, which itself was increased prior to the induction of DNA replication. This temporal sequence was observed (i) by quantitation of the induction of the base-excision repair enzyme uracil DNA glycosylase during cell proliferation in the absence of cellular insult and (ii) by quantitation of nucleotide-excision repair after UV irradiation or base-excision repair after exposure to methylmethane sulfonate. In contrast, Bloom's syndrome cells were characterized by specific alterations in this temporal sequence of gene regulation, such that DNA repair was not enhanced prior to the induction of DNA replication. Nucleotide-excision repair, base-excision repair, and the uracil DNA glycosylase were induced in a temporal sequence identical to that observed for DNA polymerase and for DNA replication. The inability of Bloom's syndrome cells to enhance DNA repair prior to DNA replication suggests that miscoding lesions remain in DNA and are replicated during cell proliferation.